IMPLEMENTATION OF THE PRINCIPLE OF GENDER JUSTICE IN ISLAMIC MARRIAGE LAW - Imam Anas Hadi (Tahta Media Group, 2025)
This study aims to analyze and evaluate the implementation of gender justice principles in Islamic marriage law at both the normative regulatory level and judicial practice. The research employs a socio-legal (normative-empirical) approach using a qualitative descriptive-analytical method. Data were collected through a literature review of statutory regulations and recent scholarly works from the last five years, as well as an analysis of Religious Court decisions related to divorce, marriage dispensation, and marital property distribution. The findings indicate that, at the normative level, Islamic marriage law in Indonesia has shown progressive developments, particularly through the revision of the minimum marriage age and the strengthening of women’s rights to initiate divorce. However, at the level of judicial practice, a gap remains between legal norms and their practical implementation, especially in the interpretation of household leadership, divorce procedures, and the recognition of women’s domestic economic contributions. The evaluation demonstrates that the implementation of gender justice principles is influenced by legal substance, judicial structure, and socio-cultural legal culture. Therefore, a maqāṣid al-sharī‘ah-based reinterpretation, enhanced gender sensitivity among judicial officers, and strengthened public legal awareness are necessary to achieve substantive justice in Islamic marriage law.